Key Factors Influencing Help-Seeking Behavior Toward Hypertension Treatment Among the Productive-Age Population - Riska Ratnawati; Mega Arianti Putri (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: Hypertension remains a major public health concern, particularly among the productive-age population, where delayed treatment-seeking behavior contributes to poor disease control and an increased risk of complications. Guided by the Health Belief Model (HBM), this study aims to identify key factors influencing help-seeking behavior toward hypertension treatment among individuals aged 15–59 years.Method: This cross-sectional study was conducted in Taman Subdistrict, Madiun City, involving 146 respondents with documented long-standing hypertension selected through purposive sampling. Data were collected using a structured Likert-scale questionnaire assessing treatment-seeking behavior and HBM constructs, including perceived seriousness, perceived vulnerability, perceived barriers, perceived usefulness, self-efficacy, and cues to action.Result: Data were analyzed using descriptive statistics, chi-squared tests, and binary logistic regression. The results showed that 72.6% of participants demonstrated positive help-seeking behavior. Multivariate analysis revealed four significant predictors: perceived vulnerability (OR = 33), perceived barriers (OR = 0.02), perceived usefulness (OR = 0.03), and self-efficacy (OR = 0.04). Within the HBM framework, perceived seriousness and cues to action were not associated with help-seeking behavior. These findings highlight the critical role of psychological and perceptual factors in shaping treatment-seeking decisions. Strengthening patients’ self-efficacy, reducing barriers, and improving understanding of treatment benefits may enhance timely care-seeking among individuals with hypertension. Future studies employing more representative sampling and longitudinal designs are recommended to confirm and extend these findings.